Novel aspect of oxytocin neurons mediating parental behavior and aversive burying behavior under the control of melanin-concentrating hormone neurons - Xiong, Tingbi; Tsuchida, Lena; Inutsuka, Ayumu; Onaka, Tatsushi; Yamada, Kazuo; Orikasa, Chitose (Frontiers in Behavioral Neuroscience, 2024)
Parental behavior comprises a set of crucial actions essential for offspring survival. In this study, a double transgenic mouse model engineered to specifically express channelrhodopsin-2 (ChR2) in paraventricular hypothalamic nucleus (PVN)–oxytocin neurons and ablate lateral hypothalamic area (LHA)–melanin-concentrating hormone (MCH) neurons was used to determine the relationship between PVN–oxytocin neurons and LHA–MCH neurons associated with parental behavior. Optogenetic stimulation of ChR2-expressing PVN–oxytocin neurons induces typical parental behavior with intact LHA–MCH neurons. However, after the partial ablation of LHA–MCH neurons, even optogenetic stimulation of PVN–oxytocin neurons failed to induce parental behavior in virgin male mice, resulting in neglect rather than parental behavior. Furthermore, approximately half of the subjects exhibited burying behavior toward pups, suggesting that pups became aversive stimuli, and male mice actively performed burying behavior to avoid these aversive stimuli. This study emphasizes the novel aspect of oxytocin neurons that could result in neglect in the absence of LHA–MCH neurons regulation.